Capital's Contribution in the Perspective of Bourdieu to Reduce Multidimensional Poverty to the Recipient of the Entrepreneurship Social Assistance - Telaumbanua, Astriyana; Lawang, Robert M.Z. (Journal of Public Representative and Society Provision, 2024)
This research focuses on capital contributions in reducing multidimensional poverty to the recipients of entrepreneurial social assistance. This study uses a qualitative approach with the phenomenological method to explore the subjective experience of seven participants who recipient the Entrepreneurship Social Assistance Program carried out by the Indonesian Ministry of Social Affairs through the Galih Pakuan Bogor Center, in Bojonggede District, Bogor Regency. This study aims to analyze how the contribution of each converted capital form can reduce the dimensions of multidimensional poverty to recipients of social entrepreneurial assistance. The findings of this study indicate that capital transformation contributes to alleviating multidimensional poverty to recipients of entrepreneurial social assistance in the economic, health, education and living standards. Interaction of various forms of capital (economic, social, embodied, objectified, and digital) can optimize the management of entrepreneurial social assistance to increase business income and sustainability. Economic capital contributes to help the education costs of family members. Social capital strengthens networks to get access to health services, reach consumers and social support for meeting basic needs and decent residence assistance. Digital capital contributes to providing information, strengthening social capital and increasing knowledge. The implications of this finding indicate that programs and policies in tackling poverty requires the integrative development of various forms of capital in the recipient of social entrepreneurial assistance. This study provides a theoretical contribution by enriching literature related to the conversion of capital in the context of multidimensional poverty and offers practical insights for the development of programs and policies for more effective poverty alleviation.